Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acsnano.6b02036
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Absorption-Based Mn2P2O7–Carbon@Reduced Graphene Oxides for High-Performance Lithium-Ion Battery Anodes

Abstract: The development of freestanding flexible electrodes with high capacity and long cycle-life is a central issue for lithium-ion batteries (LIBs). Here, we use bacteria absorption of metallic Mn(2+) ions to in situ synthesize natural micro-yolk-shell-structure Mn2P2O7-carbon, followed by the use of vacuum filtration to obtain Mn2P2O7-carbon@reduced graphene oxides (RGO) papers for LIBs anodes. The Mn2P2O7 particles are completely encapsulated within the carbon film, which was obtained by carbonizing the bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 54 publications
0
52
0
Order By: Relevance
“…Early studies on the bacterium derivatives come down to almost all of the electrochemical fields, including lithium‐ion batteries, sodium‐ion batteries, lithium–air batteries, and electrocatalysis. In this section, we will review the typical bacteria and their carbonization derivatives (e.g., Pd/PdAu/Ag/Au, SnO 2 /Fe 3 O 4 , Ni 12 P 5 , and Mn 2 P 2 O 7 ) to illustrate their potentials in the fields of electrochemical areas.…”
Section: Bacterium Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies on the bacterium derivatives come down to almost all of the electrochemical fields, including lithium‐ion batteries, sodium‐ion batteries, lithium–air batteries, and electrocatalysis. In this section, we will review the typical bacteria and their carbonization derivatives (e.g., Pd/PdAu/Ag/Au, SnO 2 /Fe 3 O 4 , Ni 12 P 5 , and Mn 2 P 2 O 7 ) to illustrate their potentials in the fields of electrochemical areas.…”
Section: Bacterium Organismsmentioning
confidence: 99%
“…i) Optical photograph, j) SEM image, and k–n) TEM–HRTEM images of a Mn 2 P 2 O 7 ‐carbon@RGO paper after annealing. (i–n) Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Bacterium Organismsmentioning
confidence: 99%
“…[18,19] Third, the SEI layer has to be flexible enough to accommodate the ineligible interface fluctuation during battery cycling without repeated breakdown/repair. [1][2][3] Due to its highest theoretical specific energy (3860 mAh g −1 ), low density (0.534 g cm −3 ), and the lowest electrochemical potential (−3.040 V vs standard hydrogen electrode), a Li metal anode has long been considered the "Holy Grail" of battery chemistry. However, native SEI can hardly meet all the requirements, which necessitates the rational design of artificial SEI.…”
mentioning
confidence: 99%
“…Nevertheless, the protective effects often wear off after prolonged battery operations. [1][2][3] Due to its highest theoretical specific energy (3860 mAh g −1 ), low density (0.534 g cm −3 ), and the lowest electrochemical potential (−3.040 V vs standard hydrogen electrode), a Li metal anode has long been considered the "Holy Grail" of battery chemistry. Inadequate thickness or compositional control of the coatings may lead to compromised SEI homogeneity and more importantly, given the limited Li-ion conductivity or poor flexibility of the coating materials, the cracking of the artificial SEI layers during cycling will induce even greater inhomogeneity on Li metal surface, exacerbating dendrite growth and side reactions.…”
mentioning
confidence: 99%
“…Previously, we reported that Al-ion batteries operate through intercalation/deintercalation of AlCl 4 − Efficient large-scale electric-energy-storage systems have always attracted extensive attention in the world. [1][2][3][4][5] In the past several decades, various promising energy-storage devices such as metal-ion batteries, [6][7][8] metal-air batteries, [9,10] and metalsulfides batteries [11][12][13] have been developed. Metal-ion batteries, especially Li-ion batteries (LIBs), are most attractive, owing to their high energy density.…”
mentioning
confidence: 99%